2010
DOI: 10.1002/anie.201000304
|View full text |Cite
|
Sign up to set email alerts
|

A Rational Approach to the Ionothermal Synthesis of an AlPO4 Molecular Sieve with an LTA‐Type Framework

Abstract: Structurally sound: The synthesis of AlPO4‐LTA zeolite in ionic liquids employs 1‐benzyl‐3‐methylimidazolium, tetramethylammonium, and fluoride ions for structuring α cages, sodalite cages, and cubes (see picture; C gray, N blue, O red, Al and P purple, F green). Selective removal of 1‐benzyl‐3‐methylimidazolium ions results in a stable AlPO4‐LTA molecular sieve. The α cages of AlPO4‐LTA framework can be evacuated while maintaining structural integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 29 publications
1
31
0
1
Order By: Relevance
“…Half of the d4r units are not fully connected with two terminal hydroxy groups in each unit, which extend into the 20-ring openings. [27][28][29][30][31] Tian and co-workers found that the addition of organic amines to 1-butyl-3-methyl imidazolium IL could affect the kineticso ft he crystallization process, resulting in the formation of aluminophosphate zeotypes with AEL, AFI, and LTA topologies, depending on the concentration of organic amines. Although the germanium silicate analogue was prepared by using the diisopropylethylmethyl ammonium cation as the SDA, the gallium phosphate analoguew as first synthesized by using quinuclidinea st he SDA and alternativelyp repared by means of an ionothermal methodw ith the ionic liquid (IL) 1ethyl-3-methylimidazolium bromide ([EMIM]Br) as both solvent and SDA.…”
Section: Introductionmentioning
confidence: 99%
“…Half of the d4r units are not fully connected with two terminal hydroxy groups in each unit, which extend into the 20-ring openings. [27][28][29][30][31] Tian and co-workers found that the addition of organic amines to 1-butyl-3-methyl imidazolium IL could affect the kineticso ft he crystallization process, resulting in the formation of aluminophosphate zeotypes with AEL, AFI, and LTA topologies, depending on the concentration of organic amines. Although the germanium silicate analogue was prepared by using the diisopropylethylmethyl ammonium cation as the SDA, the gallium phosphate analoguew as first synthesized by using quinuclidinea st he SDA and alternativelyp repared by means of an ionothermal methodw ith the ionic liquid (IL) 1ethyl-3-methylimidazolium bromide ([EMIM]Br) as both solvent and SDA.…”
Section: Introductionmentioning
confidence: 99%
“…The in situ XRD patterns of DNL-1 show that no significant loss of crystallinity occurs until the temperature reaches approximately 950 °C. Moreover, the ordered crystalline structure of DNL-1 can remain after calcination at 850 °C and subsequent exposure at room temperature with 60 % humidity for 6 d. 1-Benzyl-3-methylimidazolium chloride Al + P (None) [70] (continued) Choline chloride-2-imidazolidone Co + P (None) [55] Choline chloride-2-imidazolidone Zn + P (None) [83] (continued) Only the formally published results are included. In some cases, the products contain more than one crystalline phase…”
Section: New Zeolitic Materialsmentioning
confidence: 97%
“…Based on Rietveld refinement and NMR spectroscopy, Fayad et al suggested that the structure-directing agents 1-benzyl-3-methylimidazolium cations, tetramethylammonium cations and fluoride anions fill in the lta cages, sod cages and d4r units of AlPO-LTA respectively ( Fig. 2.10) [70]. In the structure of DNL-1, it was found that 1,6-hexanediamine molecules prefer to fill in the lta cages with random orientation, while EMIm cations present in both the lta cages and the empty space at the intersection of the 20-membered ring channels [106].…”
Section: Co-structure-directing Effectmentioning
confidence: 98%
See 1 more Smart Citation
“…However, rational design of novel materials with targeted properties (structure, composition, morphology, etc.) still remains a challenge, although some evident progress has been made by several research teams [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%